Որոշ ՄԿՄ կառույցներում հոսանքի կիսախորանարդային տեղամասի հնարավորության մասին - Մինասյան, Մելս
Աշխատանքում ցուցադրված է փորձառական արդյունք, և նրա ստացումը ենթադրաբար կապվում է բարձրաօհմ նմուշում հարստացված մերձկոնտակտային շերտի գոյացման հետ: В работе показан экспериментальный результат, получение которого предположительно связывается с образованием приконтактного обогощенного слоя, возможного в высокоомном образце. The paper shows an experimental result, the receipt of which is presumably associated with the formation of a near-contact enriched layer, which is possible in a high-resistance sample. There is a commonality between the metal-semiconductor-metal (MSM) structure and the vacuum diode, especially in terms of the starting conditions for the generation of electric current, when no inter-electrode voltages have yet been applied.
Keywords: Ֆիզիկա